1998
DOI: 10.1046/j.1365-2559.1998.00383.x
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of polarity and a dual cell population in adenoid cystic carcinoma of the breast: an immunohistochemical study

Abstract: ACC of the breast is characterized by the presence of two types of intercellular lumens, one conserving basolateral markers of normal polarity (epithelial) with the other containing basement membrane material (abutted by myoepithelial cells). Dominance of VM staining may be a hallmark of ACC, along with maintained epithelial and myoeithelial compartments. This status of advanced, normal differentiation despite local invasion may be responsible for lack of distant metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 21 publications
2
29
0
Order By: Relevance
“…Accordingly, in some breast carcinomas, neoplastic myoepithelial cells are present and appear to be functional. This is the case with the adenoid cystic carcinoma, which has a better prognosis and does not metastasize to distant sites (72). In these carcinomas, laminin is deposited, and the neoplastic luminal epithelial cells polarize correctly.…”
Section: Myoepithelial Cells In Neoplasiamentioning
confidence: 97%
“…Accordingly, in some breast carcinomas, neoplastic myoepithelial cells are present and appear to be functional. This is the case with the adenoid cystic carcinoma, which has a better prognosis and does not metastasize to distant sites (72). In these carcinomas, laminin is deposited, and the neoplastic luminal epithelial cells polarize correctly.…”
Section: Myoepithelial Cells In Neoplasiamentioning
confidence: 97%
“…Nonsentinel axillary lymph node dissection was performed in Adenoid cystic carcinoma of the breast S Azoulay et al eight cases. The median number of lymph nodes examined was 12 (range: [7][8][9][10][11][12][13][14][15][16][17][18][19]. No lymph node metastases were seen in either of these cases.…”
Section: Clinical Findingsmentioning
confidence: 99%
“…Immunohistochemical studies have shown that adenoid cystic carcinoma of the breast are estrogen receptor (ER)-negative tumors composed of a double population of cells: epithelial cytokeratin-positive cells, and myoepithelial, vimentin and S100 protein-positive cells. [7][8][9][10] Recent descriptions have identified two distinct molecular weight cytokeratins (CK) as markers of different population of breast gland epithelium; CK8/18 (low molecular weight CK) expressed by luminal cells and CK5/6 (high molecular weight CK) expressed by basal cells. 11 Stem cells, which have the capacity to differentiate towards either glandular or basal phenotype, have also been identified.…”
mentioning
confidence: 99%
“…[1][2][3] The constituent neoplastic cells are both of luminal and myoepithelial type, arranged in a wide spectrum of histological patterns, that is, trabecular, tubular-cribriform, solid, and basaloid, which usually coexist in the same tumor. [1][2][3][4][5][6][7] Most adenoid cystic carcinomas follow a favorable clinical course with a low prevalence of axillary lymph node metastases (approximately 10%). Tumors showing a predominant solid pattern of growth however reportedly have a more aggressive behavior, 8 with distant metastases despite the absence of lymph node involvement and poor 5-year overall survival.…”
mentioning
confidence: 99%